2017
DOI: 10.3389/fmicb.2017.01864
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Ruminal Fungi, Archaea, Protozoa, and Bacteria to the Methane Suppression Caused by Oilseed Supplemented Diets

Abstract: Dietary lipids can suppress methane emission from ruminants, but effects are variable. Especially the role of bacteria, archaea, fungi and protozoa in mediating the lipid effects is unclear. In the present in vitro study, archaea, fungi and protozoa were selectively inhibited by specific agents. This was fully or almost fully successful for fungi and protozoa as well as archaeal activity as determined by the methyl-coenzyme M reductase alpha subunit gene. Five different microbial treatments were generated: rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
0
18
0
1
Order By: Relevance
“…In addition, its relative abundance seemed to be favored (e.g., substrate and thermodynamics) in LME animals (Auffret et al, 2018). Candidatus Methanomethylophilus was previously identified as metabolically active in ruminants (Wang et al, 2017;Mann et al, 2018). In the same cluster as Candidatus Methanomethylophilus are the acetogens Eubacterium, Blautia, and Acetitomaculum, which are highly active H 2 sinks as recently shown in sheep (Greening et al, 2019).…”
Section: Importance Of Methanogens Explaining Differences In Ch 4 Emimentioning
confidence: 61%
See 1 more Smart Citation
“…In addition, its relative abundance seemed to be favored (e.g., substrate and thermodynamics) in LME animals (Auffret et al, 2018). Candidatus Methanomethylophilus was previously identified as metabolically active in ruminants (Wang et al, 2017;Mann et al, 2018). In the same cluster as Candidatus Methanomethylophilus are the acetogens Eubacterium, Blautia, and Acetitomaculum, which are highly active H 2 sinks as recently shown in sheep (Greening et al, 2019).…”
Section: Importance Of Methanogens Explaining Differences In Ch 4 Emimentioning
confidence: 61%
“…Bacterial populations interacting with methanogens that utilize H 2 or involved in different metabolic pathways associated with amino acids, lactate or volatile fatty acids (VFA) are known to have different effects on CH 4 emissions (Moss et al, 2000;Janssen, 2010;Wanapat et al, 2015;Kamke et al, 2016;Sa et al, 2016). In addition, several authors revealed the importance of interactions between bacteria, fungi, protists (protozoa and micro-algae) and archaea in their effects on CH 4 emissions (Kumar et al, 2015;Wang et al, 2017;Huws et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms inhabiting in the rumen contribute directly or indirectly to dietary organic matter degradation (Wang et al 2017). F. succinogenes and R. flavefaciens are two of the major cellulolytic bacterial species found in the rumen, and F. succinogenes was reported to be present in greater quantities than R. flavefaciens (Koike and Kobayashi 2001), which was confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In these herbivores, the digestion of feed takes place in the rumen, the largest compartment of a four-chambered stomach, through the combined metabolic activities of resident microbial symbionts which precede digestion by host enzymes [ 3 , 4 ]. Ruminal microorganisms, consisting of a diverse array of bacteria, methanogens, protozoa, and fungi, are organized into complex communities that work synergistically to ferment ingested feedstuffs, producing short chain fatty acids (SCFAs) and microbial proteins that can be used by their host as sources of energy and amino acids, respectively [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%